ESTIMATION OF THE PREDICTIVE EFFECT OF BODY MASS INDEX-PERCENTILE ON SKELETAL MATURATION IN A NIGERIAN POPULATION.: Body mass percentile and skeletal maturation (Nigerian Dental Journal, 2023)
Objectives: To determine the predicting the effect of BMI-index percentile on the skeletal maturation of Nigerian children. Design: A prospective cross-sectional study.Setting: This study was conducted in a tertiary health care facility in North-Central Nigeria.Participants: Children between the ages of 5-17 years consisting of 44 males and 30 females that presented in the Child Dental clinic over a period of eight months were recruited for the study.Main outcome measured: Skeletal maturation was assessed using the middle phalanx of the third finger (MP3) while the standard WHO growth chart specific for age (2-20 years) and gender was used for grading BMI-percentile. The unpaired t-test was used to compare mean chronological age of the stages of MP3 according to gender. Multinomial logistic regression used to determine the predictive effect of age, gender and BMI percentile on pubertal growth spurt.Results: The BMI-percentile had weak correlation with the pubertal growth spurt (r=0.089, p=0.448). Gender (p=0.004) and chronological age had significant (p
Keywords: Body-mass percentile, skeletal maturation